A Preliminary Study on Injury Risk Factors of Perak Athletes - Ai Choo, Lee; Yusof Baharudin, Mohd; Fariza Zainudin, Fairus; Sankaravel, Mohansundar (International Journal of Engineering and Technology, 2018)
The objective of this study is to identify the injury risk factors of Perak male and female athletes who participating in contact and non-contact sports, meanwhile to suggest preventive strategies to all the sports personnel. The research design chosen was retrospective descriptive epidemiological study. The data from this study is examined based on intrinsic risk factors (Self Induce and Attire) and extrinsic risk factors (Third Party, Environment and Equipment). The descriptive statistics was utilized to analyze the research variables. The data collected for self status in self induce factor, finding revealed that body composition (51.1%) as highest risk followed by body status to play (41.7%), self-attitude (5.8%) and age difference (1.4%). Whereby, for factor of attire, more injuries occurred due to not wearing appropriate protective gear (47.5%) compared to inappropriate footwear (34.5%) and inappropriate clothing (18.0%). The extrinsic factors of third party that lead to injuries were mostly due to opponent (89.2%), contrary to referee (10.8%) and none from audiences. There was no injury reported due to playing equipment. This study finding revealed that playing surface was reported highest (75.5%) in environment factors followed by weather (24.5%). In the nutshell, injury rates can be reduced by identifying the injury risk factors and thus the life span of high performance athletes will be prolonged. Â